Kilka uwag o podejściu eksplanacyjnym w badaniach językoznawczych - Górny, Mirosław (Humaniora. Czasopismo Internetowe, 2025)
The article highlights the importance of the process of explanation in linguistics and related sciences. Explanation is rarely used by linguists today. The descriptive approach predominates and this is because it is safer and easier. The article discusses the separation of features as elements of linguistic processes and parts of language. It then briefly discusses features as relations occurring in linguistic space. In both cases, the cognitive attractiveness of the exploratory approach is emphasised. This means that the researcher asks questions about the origin of features, their function, development and disappearance. Similar questions are asked in relation to function. The difficulties that the exploratory approach causes have been mentioned here. It generally requires the use of models to explain phenomena. Because nomothetic explanation (through laws) – as is often the case in the natural sciences – is difficult here due to the small number of laws discovered in the field of linguistics. Two examples are given of the use of a model to explain linguistic processes.